Current Sheet Statistics in the Magnetosheath - Yordanova, Emiliya; Vörös, Zoltán; Raptis, Savvas; Karlsson, Tomas (Frontiers in Astronomy and Space Sciences, 2020)
The magnetosheath (MSH) plasma turbulence depends on the structure and properties of the bow shock (BS). Under quasi-parallel ($Q_{||}$) and quasi-perpendicular ($Q_{\perp}$) BS configurations the electromagnetic field and plasma quantities possess quite distinct behavior, e.g. being highly variable and structured in the $Q_{||}$ case. %Theory and numerical simulations suggest that plasma turbulence generates coherent structures, e.g. current sheets. Previous studies have reported abundance of thin current sheets (with typical scales of the order of the plasma kinetic scales) in the $Q_{||}$ MSH, associated with magnetic reconnection, plasma heating and acceleration. Here we use multipoint observations from Magnetospheric MultiScale (MMS) \textcolor{blue}{mission, where for the first time a comparative study of discontinuities and current sheets in both MSH geometries at very small spacecraft separation (of the order of the ion inertial length) is performed}. In $Q_{||}$ MSH the current density distribution is characterized by a heavy tail, populated by strong currents\textcolor{blue}{. There is high correlation between these currents and the discontinuities associated with large magnetic shears}. Whilst, this seems not to be the case in $Q_{\perp}$ MSH, where current sheets are virtually absent. We also investigate the effect of the discontinuities on the scaling of electromagnetic fluctuations in the MHD range and in the beginning of the kinetic range. There are two (one) orders of magnitude higher power in the magnetic (electric) field fluctuations in the $Q_{||}$ MSH, as well as different spectral scaling, in comparison to the $Q_{\perp}$ MSH configurations. This is an indication that the incoming solar wind turbulence is completely locally reorganized behind $Q_{\perp}$ BS while even though modified by $Q_{||}$ \textcolor{blue}{BS} geometry, the downstream turbulence properties are still reminiscent to the ones upstream\textcolor{blue}{, the latter confirming previous observations. We show also that the two geometries are associated with different temperature anisotropies, plasma beta and compressibility, where the $Q_{\perp}$ MSH is unstable to mostly mirror mode plasma instability, while the $Q_{||}$ MSH is unstable also to oblique and parallel fire-hose, and ion-cyclotron instabilities.